Distribusi Mikrohabitat dan Infeksi Endoparasit pada Ikan Kembung (Rastrelliger sp.) yang didaratkan di PPI Kedonganan, Badung, Bali - Kandouw, Claudy Margaretha; Julyantoro, Pande Gde Sasmita; Pebriani, Dewa Ayu Angga (Journal of Marine and Aquatic Sciences, 2023)
Mackerel ( Rastrelliger sp.) is a pelagic fish commodity that has high economic value because mackerel is a consumption fish and is easily found in all sea waters in Indonesia. Mackerel is a fish that is hunted for consumption because of its high omega-3 content, so it is really necessary for us to pay attention to the quality of the mackerel from the threat of parasites that can cause disease. This research was being conducted to determine the distribution of endoparasite microhabitats, intensity, prevalence, and the relation between the length of the fish and weight of fish with the number of parasites. The research samples were collected from Kedonganan Fish Landing Base, Badung, Bali, which was carried out from October 2021 to November 2021. The research used a descriptive quantitative method and the sampling method was carried out by random sampling. The total samples of fish examined were 35 fish consisting of two species, R. Kanagurta (20 fish) and R. b rachysoma (15 fish). Endoparasites of the Anisakis genus were parasites with the highest intensity and prevalence values : 4,06 ind/fish and 82,86% with a low infection rate. The relation between the length of the fish and body weight of fish with the number of parasites was in the opposite direction and had a very low effect with a value of correlation (r) between length and the number of parasites are 0,031 and a value of correlation (r) between weight and number of parasites are 0,00547.